Bench‐top X‐ray microtomography complemented with spatially localized X‐ray scattering experiments. (4th February 2014) - Suuronen, Jussi‐Petteri; Kallonen, Aki; Hänninen, Ville; Blomberg, Merja; Hämäläinen, Keijo; Serimaa, Ritva
<x xml:space="preserve">Abstract</x> This article describes a novel experimental setup that combines X‐ray microtomography (XMT) scans with in situ X‐ray scattering experiments in a laboratory setting. Combining these two methods allows the characterization of both the micrometre‐scale morphology and the crystallographic properties of the sample without removing it from the setup. Precise control of the position of the sample allows an accurate choice of the scattering beam path through the sample and facilitates the performance of X‐ray scattering experiments on submillimetre‐sized samples. With the present setup, a voxel size of less than 0.5 µm is achievable in the XMT images, and scattering experiments can be carried out with a beam size of approximately 200 × 200 µm. The potential of this setup is illustrated with the analysis of micrometeorite crystal structure and diffraction tomographic imaging of a silver behenate phantom as example applications.